Variasi Genetik Itik Bayang Berbasis Marka Mikrosatelit Pada Lokus AY287 dan Lokus AY283 - Rusfidra, Rusfidra; Heryandi, Y.; Jamsari, Jamsari; Rahman, E. Y. (Sains Peternakan: Jurnal Penelitian Ilmu Peternakan, 2013)
West Sumatera Province has poultry genetic resource of local duck that potential in supplyeggs and duck meat. Bayang duck was set by Indonesian Agricultural Ministry in 2012 as national livestock breeds in Indonesia. Microsatellite markers are widely used as a genetic identifier because of their abundant existence, co-dominant and high polymorphic. The purpose of this study was to determine the genetic diversity of Bayang ducks based on two microsatellite loci which include AY287 and AY283. DNA substances used in the study were blood samples from 24 Bayang duck in Pesisir Selatan Regency. The isolated DNA genom from 24 blood samples of Bayang duck could be detected by gel electrophoresis. Results showed that AY287 locus has 6 alleles; allele A (108 bp), allele B (142 bp), allele C (183 bp), allele D (227 bp), allele E (272 bp) and allele F (340 bp). Both allele E and F were specific genetic markers of Bayang duck. Alleles frequencies of the AY287 locus were as follow: allele C (26,93%), allele D (19,24%), allele A (15,38%), allele B (15,38%), allele E (15,38%) and allele F (7,69%). The AY283 locus has 6 alleles consisted of allele A (230 bp), allele B (320 bp), allele C (345 bp), allele D (390 bp), allele E (450 bp) and allele F (500 bp). Allele frequencies of this marker were allele B (20,51%), allele D (20,51%), allele E (20,51%), allele A (15,39%), allele C (15,39%), and allele F (7,69%), respectively. Our finding suggest that two microsatellite markers, AY287 and AY283, were polymorphic in Bayang duck population.Key words: Bayang duck, microsatellite, AY283, AY287